Tutor Support of Learners with Special Educational Needs in Conditions of Inclusive Education - Samsonova E.V.; Mel’nik Yu.V.; Karpenkova I.V. (Клиническая и специальная психология, 2021)
Authors of the study analyze key characteristics of tutor support for students with special educational needs in the context of inclusive education. An activity model of tutor support based on the analysis of foreign and domestic research is proposed. The main goal of presented model is to create conditions for the development of active position of the individual. Individual cases of tutor support for students with autism spectrum disorders and behavioral and mental characteristics that determine various difficulties of their inclusion in the educational process are considered in the article. Due to the mentioned aspects, the problem of tutor support is actualized. Case analysis shows the relevance of a tutor's work within the framework of an activity-based approach to provide conditions for the development of a conscious involvement of students in the educational process as well as the development of an active position. Present situation requires additional research.